Bionic Design of the Bumper Beam Inspired by the Bending and Energy Absorption Characteristics of Bamboo. (2nd December 2018) - Zou, Meng; Song, Jiafeng; Xu, Shucai; Liu, Shengfu; Chang, Zhiyong
Abstract : This study conducted quasistatic three-point bending tests to investigate the effect of bamboo node on the energy absorption, bending, and deformation characteristics of bamboo. Results showed that the node had a reinforcing effect on the energy absorption and bending strength of the bamboo culm subjected to bending load. The experimental results demonstrated that nodal samples (NS) significantly outperform internodal samples without node (INS). Under the three-point bending load, the main failure mode of bamboo is the fracture failure. The node also showed split and fracture prevention function obviously. Based on that, a series of bionic bumper beams were designed inspired by the bamboo node. The FEM results indicated that the performance of bionic bumpers was better than that of a normal bumper with regard to bending strength, energy absorption, and being lightweight. In particular, the bionic bumper beam has the best performance with regard to bending, energy absorption, and being lightweight compared with the normal bumper under pole impact. The characteristic of the bionic bumper beam is higher than that of the normal bumper beam by 12.3% for bending strength, 36.9% for EA, and 31.4% for SEA; moreover, there was a mass reduction of 4.9%, which still needs further optimization.